2009
DOI: 10.1371/journal.pone.0006669
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Pyrosequencing and a Phylogenetic Microarray for Exploring Microbial Community Structures in the Human Distal Intestine

Abstract: BackgroundVariations in the composition of the human intestinal microbiota are linked to diverse health conditions. High-throughput molecular technologies have recently elucidated microbial community structure at much higher resolution than was previously possible. Here we compare two such methods, pyrosequencing and a phylogenetic array, and evaluate classifications based on two variable 16S rRNA gene regions.Methods and FindingsOver 1.75 million amplicon sequences were generated from the V4 and V6 regions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
569
0
17

Year Published

2011
2011
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 781 publications
(606 citation statements)
references
References 63 publications
20
569
0
17
Order By: Relevance
“…Although it has been reported that the V4 region used in this study displayed the highest number of correctly classified sequences, followed by the V3 and V6 regions (Claesson et al, 2009), quite a large portion of effective bacterial sequences in this study could not be assigned to any taxa of different level at the 50% threshold, indicating the extent of novel sequences captured by this study. Supplementary Figure S1 shows that the unclassified sequence portions in the total community increased from the domain level to the genus level, and were significantly different among the samples, especially at the family and genus levels.…”
Section: Diversity Of Microbial Communitiesmentioning
confidence: 54%
See 3 more Smart Citations
“…Although it has been reported that the V4 region used in this study displayed the highest number of correctly classified sequences, followed by the V3 and V6 regions (Claesson et al, 2009), quite a large portion of effective bacterial sequences in this study could not be assigned to any taxa of different level at the 50% threshold, indicating the extent of novel sequences captured by this study. Supplementary Figure S1 shows that the unclassified sequence portions in the total community increased from the domain level to the genus level, and were significantly different among the samples, especially at the family and genus levels.…”
Section: Diversity Of Microbial Communitiesmentioning
confidence: 54%
“…They have also been used in other microbial diversity studies employing the PCR-based pyrosequencing method (Claesson et al, 2009;Jesus et al, 2010;Murphy et al, 2010). The 5 0 -fused primer includes a 10 nucleotide 'barcode' inserted between the Roche 454 life Science (Branford, CT, USA) adapter primer A and the 563F primer.…”
Section: Stps and Asmentioning
confidence: 99%
See 2 more Smart Citations
“…Microarrays represent an excellent choice for the high-throughput analysis of bacterial populations, because many different probes can be placed on one slide or chip, and samples thus can be tested for the presence of many different species simultaneously samples can be interrogated directly, circumventing any need for culturing, and thus non-culturable species can be reliably detected. It's been demonstrated that microarray has a power equal to new generation sequencing (Claesson et al, 2009). Several types of microarrays have been used to identify the gut microorganisms, like community genome array, functional genome array and phylogenetic oligonucleotide array (Loy et Wu et al, 2004;He et al, 2007).…”
Section: Microarraymentioning
confidence: 99%